Spurführungsregelung eines aktiv gelenkten Radpaars für Straßenbahnen - Wei, Yunfan (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2014)
This work presents investigates the feasibility of the ""directly steered wheels (DSW)"" under operating condition of tramcars. After analyzing the wheel/rail geometric contact between track and DSW, a mathematical model has been developed to describe the lateral dynamics. Based on this model, a robust guidance controller is designed according to the µ-synthesis. The results of simulations show that the DSW with the designed controller can improve the running performance of tramcars significantly.